Hydrothermal modification of the structure of silica - Косенко, О.І.; Кустовська, А.Д. (Proceedings of National Aviation University (archive), 2009)
Hydrothermal modification of silica gels of various porous structure was investigated. The opportunity of synthesis of macroporous silica materials that can be used as blank substrate in the catalytic processes of petroleum refining and petrochemistry was shown. The results obtained were explained by peculiarity of mass transfer in the pores of various size